(untitled) (Journal of Philosophy Culture and Political Science, 2021)
Annotation. The article is devoted to the evolution of scientific ideas about spirits, deities and other sacred beings, from the Enlightenment to the present day. The author touches upon some influential schools and bright scientific ideas in anthropology, ethnology and integrative scientific projects, and also outlines the main directions of the humanitarian discussion about the ontology of spirits and related religious and magical practices. The objective of the article is the historical and epistemological conceptualization of the turn from the positivist idea of ​​“disenchanting of the world” (M. Weber) to the poststructuralist and perspectivist project “to rediscover the world’s enchantment” (E. Kohn). This turn, according to the author, became possible thanks to postcolonial reflection, the movement for the decolonization of knowledge, deconstruction of classical philosophical problems and deep postmodern criticism of the Enlightenment program, which largely contained pre-secular intentions. In the XXI century, many anthropologists began to consider local ontologies as metaphysics or foreign cultural sciences, and spirits and deities as selves or non-human actors. The development of such horizontal methodologies, made possible by the increasing penetration of philosophy and semiotics into the social sciences, led to the emergence of the so-called new (or experimental) animism (D. Haraway). It can be described as an experimental platform associated with research in the field of "anthropology on the other side of man". Such studies, in addition to their ethnographic content and philosophical justification, usually have a pronounced ideological charge. This charge lies in the ecological and heuristic significance of overcoming anthropocentrism as a whole or a number of its negative consequences. Key words: anthropology of religion, epistemology, magic, sacred, spirits, deities, ontological turn, animism, new animism, poststructuralism